2009
DOI: 10.1016/j.jfe.2008.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of three regeneration programs and application behavior among Mississippi nonindustrial private forest landowners: A two-step sample selection approach

Abstract: Various public financial assistance programs are available to nonindustrial private forest (NIPF) landowners in the United States. Many landowners have limited knowledge of these programs and have not utilized them. This study employed a two-step sample selection model to examine the determinants of NIPF landowner knowledge of three regeneration programs, and conditional on their knowledge, the determinants of the application frequency to these programs since 1996. Data were collected using a phone survey of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
17
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 15 publications
7
17
3
Order By: Relevance
“…Likely landowners were more familiar with certification programs than unlikely landowner groups, suggesting that landowners' familiarity with forest certification was positively correlated with rate of participation. This result was in line with Bell et al [43], Mercker and Hodges [47], and Sun et al [48], who reported that landowner knowledge on forest certification can positively impact their motivation/willingness to participate.…”
Section: Discussionsupporting
confidence: 90%
“…Likely landowners were more familiar with certification programs than unlikely landowner groups, suggesting that landowners' familiarity with forest certification was positively correlated with rate of participation. This result was in line with Bell et al [43], Mercker and Hodges [47], and Sun et al [48], who reported that landowner knowledge on forest certification can positively impact their motivation/willingness to participate.…”
Section: Discussionsupporting
confidence: 90%
“…Though, the majority of the landowners preferred all nine policy alternatives, relatively more preferred tax incentives over direct subsidy support such as cost-share programs. This result is consistent with the findings of earlier studies by Sun et al (2009) and Megalos and Cubbage (2000). A possible reason for it could be that landowners find cost-share programs relatively more challenging and expensive to carry out compared to tax incentive measures as indicated by Sun et al (2009).…”
Section: Discussionsupporting
confidence: 94%
“…This result is consistent with the findings of earlier studies by Sun et al (2009) and Megalos and Cubbage (2000). A possible reason for it could be that landowners find cost-share programs relatively more challenging and expensive to carry out compared to tax incentive measures as indicated by Sun et al (2009). However, landowners' ideology could also have played a role in their higher preference for tax incentive measures.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Then conditional on landowner awareness, a model was developed to determine which factors affected their use of the provisions. T-SSS analyses have been widely used in the literature to analyze cost-share programs, hunting lease markets, and other forestry-related issues [51][52][53][54][55]. Our T-SSS model examined the determinants of landowner awareness and use of tax provisions.…”
Section: Logistic Regression Analysismentioning
confidence: 99%